Bacterial infection-driven lymphomagenesis. Issue 5 (25th September 2022) - Vannata, Barbara; Pirosa, Maria Cristina; Bertoni, Francesco; Rossi, Davide; Zucca, Emanuele
Abstract : Purpose of review: The first convincing evidence for a causal relationship between bacterial infection and lymphomagenesis came from the link between gastric lymphoma and chronic Helicobacter pylori gastritis. This review will summarize the current epidemiological, clinical, and biological evidence of a causative role of bacteria in the development of malignant lymphomas, particularly, the extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue type. Recent findings: Other microorganisms have been associated with specific extranodal lymphoma sites with variable and not always definitive, evidence, including Chlamydia psittaci, Borrelia burgdorferi, Campylobacter jejuni and, most recently, Coxiella Burnetii . According to most plausible models, lymphoma growth is a consequence of continuous antigenic stimulation induced by chronic infection. However, some evidence of a direct oncogenic role of H. pylori has been provided, too. Summary: Lymphomas are not the result of a single cause but multifactorial diseases, influenced by a variety of genetic and environmental elements. Hence, ascertaining the specific contribution of bacterial infections is not always easy. Nevertheless, the eradication of the associated chronic infection may result in sustained lymphoma regression. Moreover, the association between infections and lymphoma may offer opportunities for reducing lymphoma incidence by preventing the predisposing infections or treating them early.